2021
DOI: 10.14338/ijpt-20-00086
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Lymphopenia Risks of Photon Versus Proton Therapy for Esophageal Cancer Patients

Abstract: Purpose To assess possible differences in radiation-induced lymphocyte depletion for esophageal cancer patients being treated with the following 3 treatment modalities: intensity-modulated radiation therapy (IMRT), passive scattering proton therapy (PSPT), and intensity-modulated proton therapy (IMPT). Methods and Materials We used 2 prediction models to estimate lymphocyte depletion based on dose distributions. Model I used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Also, lymphocytes in the blood may be inactivated in large fields, and the entire blood pool reflects an "organ" at risk. [42][43][44][45] Both aspects may play a role in the treatment of head and neck cancers, where combining ICI with RT is associated with numerous challenges [46][47][48] and lower clinical gain is observed compared with, for example, none-small cell lung cancer. In 2 studies investigating the benefit of RIT for head and neck squamous cell carcinoma, 49,50 no enhanced combination effect has been detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, lymphocytes in the blood may be inactivated in large fields, and the entire blood pool reflects an "organ" at risk. [42][43][44][45] Both aspects may play a role in the treatment of head and neck cancers, where combining ICI with RT is associated with numerous challenges [46][47][48] and lower clinical gain is observed compared with, for example, none-small cell lung cancer. In 2 studies investigating the benefit of RIT for head and neck squamous cell carcinoma, 49,50 no enhanced combination effect has been detected.…”
Section: Discussionmentioning
confidence: 99%
“…Modern radiation therapy techniques may have the potential to improve the responsiveness to the combination of RT and ICI: charged particle therapy with protons or heavy ions reduces the integral dose and allows an efficient sparing of lymph nodes. 36,37,45,54 It can therefore enhance lymphocyte action in RIT, potentially increasing the number of responding patients. To spare lymph nodes and keep target volumes small, also modern approaches like stereotactic body radiation therapy, 55 intraoperative radiation therapy, 56 or partial tumor irradiation 19 have demonstrated to preserve or stimulate immune competence.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown strong associations between pretreatment factors and the risk of severe RIL in various cancers 5–11 . Some of these studies have attempted to predict RIL based on different set of pretreatment parameters that are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al 10 developed a hybrid deep learning model to classify patients with grade 4 RIL based on patient characteristics and dosimetric features but they did not investigate the ALC kinetics during RT treatment for individual patients. Ebrahimi et al 11 performed a posttreatment analysis based on weekly ALC measurements for ten esophageal cancer patients and showed that the ALC depletion during the course of RT can be fitted to a piecewise-linear or an exponential model as a function of radiation dose for 10 esophageal cancer patients. However, they did not consider other significant patient-specific clinical factors in their models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation